Sosialisasi Pentingnya Zoss di SMP Negeri 55 Kota Bekasi - Deslida Saidah; Tiur Mery B. Silalahi; Subandi - (Jurnal Abdimas Transportasi & Logistik, 2021)
The background of the socialization was because there was no Safe School Zone, the large number of school children, there were always accidents in front of the school, and the behavior of road users who did not obey the rules. The purpose of this Community Service activity is to provide socialization on the importance of ZoSS to students and educators at SMP Negeri 55 with an emphasis on traffic safety for students and road users. The method of implementation is through face-to-face with the school without any students due to the covid epidemic. The explanation was through a lap top and a video that was shared with the homeroom teacher via social media to students with parental assistance. The material socialized contains: important ZoSS and signs, correct procedures when crossing the road, safe and dangerous places to cross, helmets, cycling and health protocols. The result of this socialization activity is the growth of awareness and understanding that can change student behavior in traffic safely and safely so that it becomes a habit or daily behavior. The conclusion is the hope that a ZoSS will be made in front of SMP Negeri 55 by related parties and students will become pioneers and role models in traffic in the environment: schools, homes and communities.